Investigating the Link Between FoMO and Netlessphobia in Students - Lira Erwinda; Intan Putri Aulia; Sisilia Maudy Azzahra; Rina Sakinah; Anis Nur Padillah; Aisyah Suci Maharani; Jaya Purnama; Wulandari Askoriah; Putri Nahwati; Rosada Rosada (SCHOULID: Indonesian Journal of School Counseling, 2024)
The internet is an integral part of modern life, facilitating access to information, work, research and social interaction through social media. Its existence is very relevant in this digital era. The aim of this research is to determine the relationship between fear of missing out and netlessness in 10th grade students at SMK East Jakarta 1. The research method used is a quantitative method, with Pearson correlation analysis. The population in this study was 136 students, with the sampling technique using random sampling technique so that a sample of 102 students was obtained. The research instruments used were the fear of missing out and netlessness phobia scales. The results of the study show that there is a significant relationship between fear of missing out and nettlephobia. The relationship between the two variables fear of missing out and netlessphobia has a positive relationship, meaning that the higher the fear of missing out in students, the higher the netlessphobia. Another implication of this research is the important role of schools and society in understanding and overcoming the impact of FOMO and Netlessphobia on students. This research also highlights the need for parents' role in providing healthy guidance regarding internet and social media.